Realistic inflation in no-scale U(1)R symmetric flipped SU(5). Issue 10 (8th October 2021) - Abid, Mian Muhammad Azeem; Mehmood, Maria; Rehman, Mansoor Ur; Shafi, Qaisar
Abstract: We have realized non-minimal Higgs inflation and standard hybrid inflation in the supersymmetric flipped SU(5) model with U(1) R symmetry using the no-scale form of the Kähler potential. In non-minimal Higgs inflation the waterfall Higgs field plays the role of inflaton, and in standard hybrid inflation the gauge singlet field S is employed as an inflaton. The predictions of both models are in good agreement with the Planck 2018 data. For numerical calculations we have fixed the gauge symmetry breaking scale, M, around 2 × 10 16 GeV. In both models the inflaton field values are constrained below mP . The tensor to scalar ratio r in non-minimal inflation is of the order of 10 -3 and for standard hybrid inflation r is tiny, of order 10 -15 –10 -4 . The scalar spectral index in both cases lie within the Planck 1-σ bounds, and the running of the scalar spectral index lies in the range, -d ns /d ln  k  ∼ 6 × 10 -4 for non-minimal model and 10 -9 –10 -3 for the standard hybrid model. A realistic scenario of reheating and non-thermal leptogenesis is employed with reheat temperature Tr  ∼ 10 9 GeV for non-minimal model and 10 6 –10 10 GeV for standard hybrid model. The R -symmetry plays a vital role in forbidding rapid proton decay, but at the same time it also suppresses terms responsible for generating right handed neutrino masses. A realistic scenario of right handed neutrino masses is obtained by considering effective R symmetry breaking at the nonrenormalizable level with adequate suppression of rapid proton decay.